Disability intimacy : essays on love, care, and desire - Wong, Alice, 1974- (Vintage Books, a division of Penguin Random House, LLC, 2024)
"The much-anticipated follow up to the groundbreaking anthology Disability Visibility: another revolutionary collection of first-person writing on the joys and challenges of the modern disability experience, and intimacy in all its myriad forms. What is intimacy? More than sex, more than romantic love, the pieces in this stunning and illuminating new anthology offer broader and more inclusive definitions of what it can mean to be intimate with another person. Explorations of caregiving, community, access, and friendship offer us alternative ways of thinking about the connections we form with others-a vital reimagining in an era when forced physical distance is at times a necessary norm. But don't worry: there's still sex to consider-and the numerous ways sexual liberation intersects with disability justice. Plunge between these pages and you'll also find disabled sexual discovery, disabled love stories, and disabled joy. These twenty-five stunning original pieces-plus other modern classics on the subject, all carefully curated by acclaimed activist Alice Wong-include essays, photo essays, poetry, drama, and erotica: a full spectrum of the dreams, fantasies, and deeply personal realities of a wide range of beautiful bodies and minds. Disability Intimacy will free your thinking, invigorate your spirit, and delight your desires"--